Capital Controls: A Pragmatic Proposal - Maria Socorro Gochoco-Bautista; Changyong Rhee (Asian Development Bank (ADB), 2013)
The strong and volatile rebound of capital inflows, mostly portfolio investments, into emerging economies in the recovery process of the 2008 global financial crisis has brought the issue of capital controls to the forefront once again. The presence of global imbalances and unconventional monetary easing in advanced countries has added new complexity to the controversy surrounding their use, as `currency wars' became a hot button political issue. While the International Monetary Fund's (IMF) recent openness to the use of capital controls has drawn positive reactions from emerging economies, its framework is still perceived as complicated, intentionally vague, and difficult to implement. To complement the IMF's new framework and make it easier to operationalize, this paper proposes a pragmatic approach to the use of capital controls which leverages the G20 indicative guidelines in measuring excessive imbalances in order to simplify the IMF's guidelines on the use of capital controls. Our proposal, which argues for the absence of persistent current account imbalances as a precondition to the use of capital controls, is anchored on the principle that a country's sovereign right to use all available tools and implement policies that they deem best should be respected as long as there are no substantial negative externalities on other countries.
hdl:11540/2332
Keywords: 330; capital controls; financial stability; global imbalances; G20; indicative guidelines; Finanzkrise; Kapitalverkehrskontrolle; G20-Staaten